Proposta de novo método de aplicação da TENS e eficácia clínica em mulheres com dismenorréia primária: estudo controlado randomizado duplo cego - Camilo, Fábio Mendes (2014)
Transcutaneous electrical nerve stimulation (TENS) is a non-pharmacological technique used to relieve pain. In general, the literature states that the analgesic results obtained with TENS are true, but when subjected to a statistical analysis did not show significant, hindering the development of an efficient and statistically significant script for the application of TENS. For that, we developed strategies that may increase the analgesic effectiveness of TENS, suggest a new methodology for their application form, using in a primary dysmenorrhea pain model to test its effectiveness. Where the first two studies aimed to verify the potential analgesic of the proposed method (interactive TENS) in primary dysmenorrhea were performed. Volunteers (124) between 18 to 36 years old with primary dysmenorrhea were randomly allocated into two groups: (A) iTENS (n=62) and (B) placebo (n=62) received a single application in a single menstrual cycle. Pain intensity was assessed using the Visual Analogue Scale (VAS) before and after application. Data were analyzed using independent t test to compare the effect of iTENS versus placebo (p <0.01). Results with VAS show a significant reduction in pain intensity for both groups: group A of 7.58 (± 1.36) before to 0.01 (± 0.05) after application and in group B 7.65 (± 1.28) to 7.0 (± 1.36). However, the total number of participants who received iTENS application, 93.5% reported effective analgesia, with an average duration of 8.5 hours, and 22.5% of them there was no return of dysmenorrhea during the next menstrual cycle. The second study aimed to examine the therapeutic effects of interactive TENS in the treatment of primary dysmenorrhea, and verify that the concentration of salivary cortisol can be used as a quantitative tool as measurement of analgesia. Volunteers (36) between 18 to 36 years with primary dysmenorrhea were randomly allocated into two groups: Group A (n=17) received an application of iTENS in three menstrual cycles (consecutive) and Group B (n=19) received a placebo TENS application in a single menstrual cycle, wherein the duration of each application was 35 minutes. The evaluation was accomplished through the following analysis: pain intensity was assessed by VAS; salivary cortisol level by electrochemical-luminescence; physical discomfort associated with dysmenorrhea by Smith Pregnancy Discomfort Intensity Index (SPADI); depressive state, by the Beck Depression Inventory (Beck Depression Inventory) (BDI) and quality of life with the WHOQOL-Bref. Data were statistically analyzed with the Statistica software, and the normality by Shapiro-Wilk test, pre and post treatment effects (both groups) by the nonparametric Wilcoxon test and comparison of data between groups after treatment adopted the non parametric test Mann-Whitney. The level of significance was 5% (p≤0.05). Comparing the results obtained analgesia between groups (after the first application), we notice a significant decrease (p<0.001) in VAS score in the group of iTENS, with an average duration of analgesia of 7.1 hours. There was an average reduction of salivary cortisol levels in volunteers from both groups, but the reductions intra-group and inter-group were not significant. Furthermore, treatment with the iTENS provided a significant reduction in the use of analgesic medications, the physical discomforts associated with dysmenorrhea and a real improvement in the quality of life of treated group (A). We can concluded that iTENS method besides being an effective palliative feature is also potentially curative for primary dysmenorrhea. The level of salivary cortisol is not adequate to evaluate the analgesic response in dysmenorrhea promoted by iTENS in pain index. However, other studies should be conducted with the aim to confirm these results.